Dressing monitoring with a digital signal processor - Luzia, R. F. [UNESP]; de Aguiar, P. R. [UNESP]; Bianchi, E. C.; Spadotto, M. M. [UNESP] (Wit Press, 2010)
Grinding is a finishing process in machining operations, and the topology of the grinding tool is responsible for producing the desired result on the surface of the machined material The tool topology is modeled in the dressing process and precision is therefore extremely important This study presents a solution in the monitoring of the dressing process, using a digital signal processor (DSP) operating in real time to detect the optimal dressing moment To confirm the monitoring efficiency by DSP, the results were compared with those of a data acquisition system (DAQ) and offline processing The method employed here consisted of analyzing the acoustic emission and electrical power signal by applying the DPO and DPKS parameters The analysis of the results allowed us to conclude that the application of the DPO and DPKS parameters can be substituted by processing of the mean acoustic emission signal, thus reducing the computational effort
Keywords: data acquisition; digital signal processor; dressing operation; grinding process